Impact of low resolution on image recognition with deep neural networks: An experimental study - Koziarski, Michał; Cyganek, Bogusław (Zielona Góra: Uniwersytet Zielonogórski)
Due to the advances made in recent years, methods based on deep neural networks have been able to achieve a state-of-the-art performance in various computer vision problems. In some tasks, such as image recognition, neural-based approaches have even been able to surpass human performance. However, the benchmarks on which neural networks achieve these impressive results usually consist of fairly high quality data.
Keywords: image recognition; deep neural networks; convolutional neural networks; low resolution; super-resolution